Assessing the value of action research: Using a world café to explore the professional journey of nurse educators - van Wyngaarden, A.; Leech, R.; Coetzee, I.M. (South African Journal of Higher Education, 2018)
Nurse educators play a crucial role in the development of student nurses’ clinical reasoning skills. To promote clinical reasoning skills, nurse educators should identify and implement appropriate student-centred teaching practices. We used the World Café data collection method to explore nurse educator’s professional journey through action research. We describe how action research, participating in the study and collaborative inquiry changed teaching practices. Action research contributed to nurse educators’ professional development, allowing them to reflect on own practices and develop critical thinking and clinical reasoning skills. Nurse educators reported using more student-centred teaching and learning practices. We describe the World Café method, which we used to collect data. The method can also be used in nursing education as a teaching strategy, students can explore various topics of interest whilst developing competencies in communication, building relationships and collaborative learning.